“Transport Me Away”: Fostering Flow in Open Offices through Virtual Reality - Ruvimova, Anastasia; Kim, Junhyeok; Fritz, Thomas; Hancock, Mark; Shepherd, David C. (ACM, 2020)
Open offices are cost-effective and continue to be popular. However, research shows that these environments, brimming with distractions and sensory overload, frequently hamper productivity. Our research investigates the use of virtual reality (VR) to mitigate distractions in an open office setting and improve one's ability to be in flow. In a lab study, 35 participants performed visual programming tasks in four combinations of physical (open or closed office) and virtual environments (beach or virtual office). While participants both preferred and were in flow more in a closed office without VR, in an open office, the VR environments outperformed the no VR condition in all measures of flow, performance, and preference. Especially considering the recent rapid advancements in VR, our findings illustrate the potential VR has to improve flow and satisfaction in open offices.
© {Anastasia Ruvimova, Junhyeok Kim, Thomas Fritz, Mark Hancock, David C. Shepherd| ACM} 2020. This is the author's version of the work. It is posted here for your personal use. Not for redistribution. The definitive Version of Record was published in Association for Computing Machinery, https://doi.org/10.1145/3313831.3376724
Keywords: virtual reality; open offices; flow; work